The usefulness of human biomonitoring in the case of mycotoxins exposure assessment - Viegas, Susana (2021)
Human Biomonitoring (HBM) has been identified as a promising tool to assess the exposure to contaminants from different origins, providing information of aggregated exposures from different routes and contributing to the establishment of the total body burden of an individual. Mycotoxins are fungi metabolites produced by specific fungal genera that can resist adverse environmental factors making it difficult to eliminate or inactivate from the source even after being exposed to culinary processes. Therefore, the most common exposure source is the diet but exposure in indoor and occupational environments has already been reported. This article highlights the usefulness of HBM when performing mycotoxins exposure assessment and the support that HBM data can give to risk management measures and policy actions in order to reduce exposure.